Sleep timing and child and parent outcomes in Australian 4-9-year-olds: a cross-sectional and longitudinal study - Quach, Jon; Bittman, Michael; Hiscock, Harriet; Price, Anna M H (My University, 2016)
OBJECTIVES: The aim of this study is to use national Australian time-diary data to examine both (1) cross-sectionally and (2) longitudinally whether being late versus early to sleep or wake is associated with poorer child behavior, quality of life, learning, cognition and weight status, and parental mental health. METHODS: DESIGN/SETTING: Data from the first three waves of the Longitudinal Study of Australian Children were taken. PARTICIPANTS: A national representative sample of 4983 4-5-year-olds, recruited in 2004 from the Australian Medicare database and followed up biennially, was taken; 3631 had analyzable sleep information and a concurrent measure of health and well-being for at least one wave. MEASURES: EXPOSURE: Parents completed 24-h child time-use diaries for one week and one weekend day at each wave. Using median splits, sleep timing was categorized into early-to-sleep/early-to-wake (EE), early-to-sleep/late-to-wake (EL), late-to-sleep/early-to-wake (LE), and late-to-sleep/late-to-wake (LL) at each wave. OUTCOMES: The outcomes included parent-reported child behavior, health-related quality of life, maternal/paternal mental health, teacher-reported child language, literacy, mathematical thinking, and approach to learning. The study assessed child body mass index and girth. RESULTS: (1) Using EE as the comparator, linear regression analyses revealed that being late-to-sleep was associated with poorer child quality of life from 6 to 9 years and maternal mental health at 6-7 years. There was inconsistent or no evidence for associations between sleep timing and all other outcomes. (2) Using the count of the number of times (waves) at which a child was categorized as late-to-sleep (range 0-3), longitudinal analyses demonstrated that there was a cumulative effect of late-to-sleep profiles on poorer child and maternal outcomes at the child age of 8-9 years. CONCLUSIONS: Examined cross-sectionally, sleep timing is a driver of children's quality of life and maternal depression. Examined longitudinally, there appears to be cumulative and adverse relationships between late-to-sleep profiles and poorer child and maternal outcomes at the child age of 8-9 years. Understanding how other parameters - such as scheduling consistency, sleep efficiency and hygiene - are also related to child and parent outcomes will help health professionals better target sleep management advice to families.
Sleep Medicine
Keywords: Childhood and child development; Childhood and child development